CMOS image sensor capable of performing analog correlated double sampling (2005)
A complementary metal oxide semiconductor (CMOS) image sensor capable of performing an analog correlated double sampling method is provided. The CMOS image sensor includes an image capturing unit for capturing an analog signal corresponding to an image of a subject; an analog-digital converting unit for converting the analog signal into a digital signal by using a ramp signal decreasing in a fixed slope according to a reference clock; a ramp signal generation unit for providing the ramp signal to the analog-digital converter; and a control unit for providing said units with control signals and outputting data to the outside through an interface.